Iatrogenic Periorbital Subcutaneous Emphysema after Endodontic Treatment – A Case Report. - Shashidhar , C.; Sarda, Poonam Narayan; Parmar, Jenish; Patil, Sayli (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Surgical emphysema is well known and many case reports have been published on this. Many authors have reported this as a complication post dentoalveolar treatment. Diffusion of air into facial planes and periorbital area during endodontic procedures has been rarely reported. The use of three-way air syringe and forceful irrigation of root canal can lead to surgical emphysema of subcutaneous tissue planes in and around the teeth which are involved. CASE REPORT: This case report highlights one such complication seen during endodontic treatment and conservative management of this dental office emergency. CONCLUSION: Endodontic treatment is not frequently associated with the presence of the SCE. However, it is very important to know how to recognize this situation when occurs, to treat the patient appropriately.